EL DESPOBLADO ISLÁMICO DE <<VILLA VIEJA>>, CALASPARRA (MURCIA). MEMORIA PRELIMINAR - Pozo Martínez, Indalecio (Miscelánea Medieval Murciana, 1989)
The following is a detailed analysis of the archeological excavations of the «Villa Vieja» settlement near Calasparra in the región of Murcia. The remains represent a rural Islamic farmstead which was built up during the 10th, llth and 12th centuries and disinhabited in the latter half of the 13th as a result of the Castilian conquest of the area or, possibly, the Mudejar revolt of 1264-66. Particular attention is given to the defences, road network, dwellings and materials and means of construction